Exploring the short-term effects of the Strengthening Families Program on Brazilian adolescents: a pre-experimental study. (4th May 2021) - Murta, Sheila Giardini; Vinha, Luís Gustavo do Amaral; Nobre-Sandoval, Larissa de Almeida; Rocha, Viviane Paula Santos; Duailibe, Karina Damous; Gomes, Maria do Socorro Mendes; Farias, Danielle Aranha; Foxcroft, David
Abstract: Background: Substance abuse and violence are among the primary health concerns regarding Brazilian adolescents. This study sought to explore the short-term effects of the Strengthening Families Program (SFP 10-14), a preventive program for families with adolescents, adapted to Brazil. Methods: A pre-experimental design was used, with a pretest and 10-12-month follow-up evaluation. A qualitative study was carried out using in-depth interviews held one to three months after the intervention to examine the use of skills learned. The sample included 126 adolescents (pre-test and follow-up comparison) and 23 adolescents (interviews) between 10 and 14 years of age from low-income families residing in northeastern Brazil. Results: The comparison between pretest and follow-up showed an increase in learning self-efficacy and school absence without parental permission. Null effects were found on the consumption of alcohol in the last month; episodes of binge drinking in the last month; antisocial behavior; parenting practices regarding emotional support factors, intrusiveness, and behavior supervision; future time perspective; doing homework; grade repetition; school grades; school dropout; and satisfaction with one's relationship with school. The majority of the interviewed adolescents reported applying the learned skills during family interaction and with friends. Conclusion: Mixed results were found on short-term effects of the Strengthening Families Program for Brazilian adolescents. Future studies should examine the contexts and mechanisms linked to such results.